SWITCHING DEVICE WITH AN ISOLATING OR EARTHING FUNCTION - NIKOLIC, Paul Gregor; REICHERT, Frank (2024)
A switching device has an isolating or earthing function. The switching device contains an encapsulation housing filled with an insulating gas, a first contact arrangement with a first main contact and a first arc contact, a second contact arrangement with a second main contact and a second arc contact, and a nozzle arrangement which is configured to subject a switching arc between the arc contacts to an insulating gas flow. The contact arrangements are moveable relative to one another between a first end position and a second end position. During the movement from the first end position to the second end position, the main contacts are isolated from one another upstream of the arc contacts and a switching arc between the arc contacts is quenched by subjecting the switching arc to an insulating gas flow.